2013
DOI: 10.1371/journal.pone.0072076
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Response of Hemocytes of the Insect Oncopeltus fasciatus against the Flagellate Phytomonas serpens

Abstract: The genus Phytomonas includes parasites that are etiological agents of important plant diseases, especially in Central and South America. These parasites are transmitted to plants via the bite of an infected phytophagous hemipteran. Despite the economic impact of these parasites, many basic questions regarding the genus Phytomonas remain unanswered, such as the mechanism by which the parasites cope with the immune response of the insect vector. In this report, using a model of systemic infection, we describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Taken together, these early investigations suggested that individual Phytomonas species may be spread between plant hosts by a broad range of different insects. Consistent with these early reports, all subsequent evidence suggests that Phytomonas are transmitted by phytophagous insects [ 45 , 56 , 57 ]. Though the relationship between plant host, parasite, and insect host appears simple ( S1 Table ), in reality it is unknown to what extent different Phytomonas species can be spread by different insects or can colonise different plants.…”
Section: Transmission and Life Cyclesupporting
confidence: 76%
See 1 more Smart Citation
“…Taken together, these early investigations suggested that individual Phytomonas species may be spread between plant hosts by a broad range of different insects. Consistent with these early reports, all subsequent evidence suggests that Phytomonas are transmitted by phytophagous insects [ 45 , 56 , 57 ]. Though the relationship between plant host, parasite, and insect host appears simple ( S1 Table ), in reality it is unknown to what extent different Phytomonas species can be spread by different insects or can colonise different plants.…”
Section: Transmission and Life Cyclesupporting
confidence: 76%
“…This is in contrast to Leishmania and Trypanosoma where cultured insect adapted cells are not infective to mammalian hosts and metacylogenesis must be induced prior to infection [ 63 ]. Though a preadapted metacyclic stage may not be present in the Phytomonas life cycle, P. serpens cells have been observed to attach to insect salivary glands [ 56 ] indicative of a true developmental stage inside the insect host.…”
Section: Transmission and Life Cyclementioning
confidence: 99%
“…Total haemocyte count losses have also been reported following treatment of Reticulitermes fl avipes with Metarhizium anisopliae, or the shield bug, Eurygaster integriceps Puton (Hemiptera: Scutelleridae) with B. bassiana and its secondary metabolites (Chouvenc et al, 2009;Zibaee et al, 2011). However, the challenge of Oncopeltus fasciatus with Phytomonas serpens induced a signifi cant increase in haemocyte count (Alves e Silva et al, 2013). The observed increase in haemocyte number could be due to pathogen stimulation of the host haematopoiesis, followed by a depletion caused by the immune response activity of the haemocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The haemocytes thus obtained were washed 3 times with cold 1 × PBS (each for 5 min) and re-suspended in 50 μl of SF9 cell culture medium. Then 3 μl of (Blattodea: Isoptera: Rhinotermitidae) or Phytomonas serpens-induced Large milkweed bugs, Oncopeltus fasciatus (Dallas) (Hemiptera: Lygaeidae) increased signifi cantly, while the pool of circulating haemocytes became depleted in Bacillus thuringiensis-infected Greater wax moths, Galleria mellonella (L.) (Lepidoptera: Pyralidae) (Chouvenc et al, 2009; Alves e Silva et al, 2013). In Macrocentrus cingulum-parasitized Asian corn borer moth larvae, Ostrinia furnacalis (Guenée) (Lepidoptera: Crambidae), the total number of haemocytes remained unchanged for 4 days, but decreased signifi cantly 5 days post parasitization (Hu et al, 2003).…”
Section: Effect Of Plasma On Phagocytosis and Nodulation In O Furnacmentioning
confidence: 99%
“…Insects defend themselves against pathogens and parasites with their effective innate immune system, which is divided into humoral and cellular responses (Beck and Strand, 2007; Strand, ). The humoral responses refer to the production of antimicrobial peptides, complement‐like proteins, reactive intermediates of oxygen or nitrogen, and the complex enzymatic cascades that regulate coagulation and melanization of hemolymph (Alves et al., ). The cellular responses in contrast involve phagocytosis, nodulation, and encapsulation that are mediated by hemocytes (Er et al., ).…”
Section: Introductionmentioning
confidence: 99%